2012
DOI: 10.1002/smll.201102393
|View full text |Cite
|
Sign up to set email alerts
|

Hemocompatibility and Macrophage Response of Pristine and Functionalized Graphene

Abstract: Graphene and its derivatives are being proposed for several important biomedical applications including drug delivery, gene delivery, contrast imaging, and anticancer therapy. Most of these applications demand intravenous injection of graphene and hence evaluation of its hemocompatibility is an essential prerequisite. Herein, both pristine and functionalized graphene are extensively characterized for their interactions with murine macrophage RAW 264.7 cells and human primary blood components. Detailed analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
253
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(272 citation statements)
references
References 59 publications
10
253
1
Order By: Relevance
“…[ 31 ] These optical properties combined with biocompatibility have rendered them ideal candidates for further functionalization and exploitation for fl uorescent bioimaging. [ 30,31,33 ] The assembly process between NDIs and nanomaterials such as C 60 , C 70 , and SWNTs has been explored, by us and others. [ 33,[35][36][37] Recently, an interest in understanding their interactions with planar carbon system (denoted here PCS) has emerged and these are believed to be based on noncovalent contacts such as π-stacking coupled with hydrophobic interactions and Coulombic attractions of the electron deficient NDI core to the electron rich surface of graphene and its derivatives.…”
Section: Thermally Reduced Graphene Oxide Nanohybrids Of Chiral Functmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 31 ] These optical properties combined with biocompatibility have rendered them ideal candidates for further functionalization and exploitation for fl uorescent bioimaging. [ 30,31,33 ] The assembly process between NDIs and nanomaterials such as C 60 , C 70 , and SWNTs has been explored, by us and others. [ 33,[35][36][37] Recently, an interest in understanding their interactions with planar carbon system (denoted here PCS) has emerged and these are believed to be based on noncovalent contacts such as π-stacking coupled with hydrophobic interactions and Coulombic attractions of the electron deficient NDI core to the electron rich surface of graphene and its derivatives.…”
Section: Thermally Reduced Graphene Oxide Nanohybrids Of Chiral Functmentioning
confidence: 99%
“…[ 67 ] Although the mechanisms for their toxicity toward cells are not completely understood as they follow different paths, [ 68 ] the formation of reactive oxygen species seems to be the most recurring mechanism observed. [ 69,70 ] While pristine carbon based materials tend to accumulate in physiological solution due to electrostatic interactions and nonspecifi c bindings to proteins, [ 71 ] surface-modifi ed graphene-like materials are often deemed to be less toxic. [ 70,72 ] Our results are consistent with these observations.…”
Section: Advmentioning
confidence: 99%
See 1 more Smart Citation
“…RAW 264.7 macrophages treated with pristine graphene were found to show increased ROS generation and impairment of mitochondrial membrane potential and cell death by inducing MAP kinases and transforming growth factor-beta-related signaling pathways. 172,173 Recently, we found that resveratrol-reduced GO induced more toxic effects than GO in human ovarian cancer cells by increasing LDH release, ROS generation, activation of caspase-3, and DNA fragmentation. 113 For example, GO reduced by Typha angustifolia leaf extract induced apoptosis by causing morphological changes (Figure 2).…”
mentioning
confidence: 99%
“…Initial studies examining the hemocompatibility of graphene and GO showed that graphene exerted a slightly higher cytotoxic effect than GO due to its strong hydrophobic interaction with cell membranes with both materials exerting insignificant hemolytic effect (up to 75 µg/ mL). 167 In contrast, Liao et al 168 demonstrated that submicronsized GO sheets induced the greatest hemolytic activity, whereas aggregated graphene sheets exhibited the lowest hemolytic activity. Coating the oxidized sheets with chitosan almost eliminated hemolytic activity.…”
mentioning
confidence: 97%